Doing time, writing lives: refiguring literacy and higher education in prison - Berry, Patrick W. (Southern Illinois University Press, 2018)
Introduction: a perspective on literacy, hope, and mass incarceration -- Doing time with literacy narratives -- Prison business: professional writing and the contextual now -- Remembering literacy: teachers' pathways to and from prison -- Literacy, life, and mobility after prison